The Effect of Sports Classes on the Quality of Life of Older Adults in Sidakarya Village - Ni Wayan Mariani; Ni Luh Putu Dian Yunita Sari; Si Putu Agung Ayu Pertiwi Dewi (Jurnal Kesehatan, 2025)
Introduction: Quality of life is a person's assessment of their position in life including physical, psychological, and social aspects and the overall level of life satisfaction. Efforts to improve the quality of life of older adults through physical activity by providing sports classes. The purpose of this study was to determine the effect of sports classes on the quality of life of older adults in Sidakarya Village. Method: The research method used is Pre Experimental One-Group Pretest-Posttest Design. The research sample was 76 senior people in the Sidakarya Village area who were selected using purposive sampling techniques that met the sample criteria. Data were collected using a quality-of-life questionnaire sheet, namely the World Health Organization Quality of Life (WHOQOL) with 20 question items that had previously been tested for validity and reliability. Data were analyzed using the Wilcoxon Signed Rank Test statistical test. Results: The results of the study showed an increase in the quality of life in older adults towards the better after being given treatment in the form of sports classes. Statistically, it showed that there was an effect of sports classes on the quality of life in older adults in Sidakarya Village (p value 0.00; α = 0.05). Conclusion: The quality of life of older adults before being given treatment in Sidakarya Village, most respondents were in the bad category (59.2%). The quality of life of older adults after being given treatment in Sidakarya Village, most respondents were in the good category (72.4%). It is hoped that the elderly will remain routine and more active in participating in sports classes held by posyandu cadres assisted by health workers. Protocol registration: This research has previously passed ethical review with the number: 023/EA/KEPK-BUB-2025